Fundamentals of Entrepreneurship (Ent300) : Case Study D’BORNEO / Mohd Syafiq Afiq Saini ...[et al.] - Saini, Mohd Syafiq Afiq; Francis, Ferris; Frankie Dahing, Felix Micky; Mazen, Mary Azira; Baja, Dorathy (2015)
D’ Borneo establish to provide and promote local clothing brand selected in D’Borneo design talent. As entrepreneurs, we take this as an opportunity to open up a business regarding to local brand scene.Our main priorities are the satisfactory of our customers’ demands and provide them the best price in our store. Our location, which is at Electra House , Jalan Power,9300 Kuching , Sarawak, the location is strategic as we can attract students, tourist and compete with the existing international brand market at nearby shopping complex like Nike , F.O.S , Adidas and many more.